Effectiveness of Using Mini Drama to Enhance Students' Speaking Skills at SMK Prima Bekasi - Farah Ghina Salsabila (INDO PUBLISHING, 2025)
This study explores how effective minidrama can be as a tool to improve students’ speaking skills at SMK PRIMA BEKASI. Speaking in English is often one of the most difficult skill for students to master. Many struggle with pronunciation, vocabulary, and grammar and even more with confidence when speaking in front of others. That’s why it’s important to find learning methods that are not only educational but also engaging and enjoyable. The research used a quasi- experimental desind with two group of eleven grade students. The experimental group was taught using mini drama, where students worked in groups to perfom short drama scenes. Meanwhile, the control group learned speaking through more traditional methods like class discussions and Q and A sessions. Both groups took a pre- test and post- test to track their progress. The results showed that students who participated in mini drama activities showed greater improvement in their speaking skills. They became more confident, used more appropriate vocabulary and grammar, and were more fluent in expressing themselves. Besides that, the learning atmosphere became more fun and dynamic, which made students more enthusiastic and involved during class. In conclusion, mini drama is an effective and enjoyable way to help students develop their English speaking skills. It not only improves their language ability but also boosts their confidence and classroom participation. Teachers, especially in vocational schools like SMK PRIMA BEKASI, are encouraged to integrate this method into their speaking lessons.